2019
DOI: 10.2174/1570161116666180101165306
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stenosis, Aortic Regurgitation and Arterial Hypertension

Abstract: Several lines of evidence support a detrimental association between HT and aortic valve disease. Therefore, HT should be promptly treated in aortic valvulopathy. Despite conventional wisdom, specific vasodilators can be used with caution in aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 98 publications
0
30
1
1
Order By: Relevance
“…Perhaps common molecular mechanisms that are important for LV remodeling in AS and HT could provide an answer about this intriguing relationship. Growth‐stimulating signals such as angiotensin I and catecholamines produced in the hypertrophic LV and outside LV in AS and even more in HT might induce RV remodeling and functional deterioration in AS . The hemodynamic change is common for AS and HT—significant increase in afterload and well‐known activation of the renin‐angiotensin‐aldosterone system could also have an important role in further deterioration of RV function in AS patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Perhaps common molecular mechanisms that are important for LV remodeling in AS and HT could provide an answer about this intriguing relationship. Growth‐stimulating signals such as angiotensin I and catecholamines produced in the hypertrophic LV and outside LV in AS and even more in HT might induce RV remodeling and functional deterioration in AS . The hemodynamic change is common for AS and HT—significant increase in afterload and well‐known activation of the renin‐angiotensin‐aldosterone system could also have an important role in further deterioration of RV function in AS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies demonstrated significant prevalence of arterial hypertension (HT) in AS patients, which reaches almost 80% in the older population . The impact of HT on AS severity assessment is still controversial . It is known that changes in blood pressure induce concomitant changes in transvalvular flow rate that results in over‐ or underestimation of AS severity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations